2011
DOI: 10.1080/14631377.2011.570037
|View full text |Cite
|
Sign up to set email alerts
|

What is success and what is failure of transition? A critical review of two decades of agricultural reform in the Europe and Central Asia region

Abstract: This article reviews the outcome of the transformation of a centrally planned into a market economy over the past two decades in the case of agriculture in the Europe and Central Asia (ECA) region. It focuses on the question of how transition progress in the region's agriculture can be evaluated and compared adequately. The article presents a set of arguments to question some of the conventional wisdom in the existing literature on what success and failure are in the transition of the ECA region's agriculture.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Moreover, the cropland suitability map may contain inaccuracies due to imperfect input data and limitations of the spatial regression model. Maybe more importantly, the location of sown areas also depends on factors not considered here, such as institutional support for agriculture [ Wandel et al ., ], farm productivity [ Bokusheva and Hockmann , ], path dependency in agricultural production, and changes in rural demography [ Ioffe and Nefedova , ]. Improvements in accuracy of cropland maps are possible with finer agricultural inventory statistics, particularly on yields and sown areas, and more precise geophysical data.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the cropland suitability map may contain inaccuracies due to imperfect input data and limitations of the spatial regression model. Maybe more importantly, the location of sown areas also depends on factors not considered here, such as institutional support for agriculture [ Wandel et al ., ], farm productivity [ Bokusheva and Hockmann , ], path dependency in agricultural production, and changes in rural demography [ Ioffe and Nefedova , ]. Improvements in accuracy of cropland maps are possible with finer agricultural inventory statistics, particularly on yields and sown areas, and more precise geophysical data.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the reform has been piecemeal, partial and subject to capture of vested interests (Arnold & Quelch, 1998;Khanna, Palepu, & Sinha, 2005) and some evidence exists that liberalization has even failed (Wandel, Pieniadz, & Glauben, 2011;Williams, Nadin, & Rogers, 2011). Moreover, the trajectory of some states, such as Belarus and those in Central Asia, was toward new forms of dictatorship rather than liberal democracy (Holmes, 2013).…”
Section: Eeca's Institutional Spectrummentioning
confidence: 95%
“…Improving crop productivity in the farming sector clearly plays a central role in promoting economic growth, increasing food security, and alleviating poverty in the country. As the literature review from developing and transitional countries has shown, efficiency enhancements in using resources positively impact crop productivity [1][2][3]. Given the various agricultural programs and policies implemented over the years to increase farmers' efficiency and productivity in Uzbekistan, it was necessary to quantitatively measure the current levels of efficiencies and their determining factors.…”
Section: Introductionmentioning
confidence: 99%